1999
DOI: 10.1002/1531-8257(199909)14:5<808::aid-mds1014>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Velocity modulation and rhythmic synchronization of gait in Huntington's disease

Abstract: This study analyzed the ability of patients with Huntington's disease (HD) to modulate gait velocity without external sensory cues and in response to an auditory rhythmic cue within a frequency entrainment design. Uncued gait patterns of 27 patients were first assessed during normal, slower, and faster self‐paced walking. During rhythmic trials, metronome and musical beat patterns were delivered at rates 10% slower and 10–20% faster than baseline cadence to cue gait patterns. After the rhythmic trials, patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
85
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 22 publications
9
85
2
Order By: Relevance
“…8 However, apathy, depression, motor problems, and inadequate transportation present exercise barriers. 13 Programs that are enjoyable, motivating, and home-based may overcome these barriers. 8 Research has shown that video game-based exercise increases practice volume, attention span and compliance compared with traditional exercise programs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 However, apathy, depression, motor problems, and inadequate transportation present exercise barriers. 13 Programs that are enjoyable, motivating, and home-based may overcome these barriers. 8 Research has shown that video game-based exercise increases practice volume, attention span and compliance compared with traditional exercise programs.…”
Section: Introductionmentioning
confidence: 99%
“…The game incorporates balance training methods (multidirectional stepping), attentional strategies (performance biofeedback), and external cueing (step synchronization to music), which are recommended for individuals with basal ganglia disorders. 13,14 Thus, Dance Dance Revolution may help overcome exercise barriers while targeting motor deficits in people with basal ganglia disorders. To date no studies have examined the use of video games as an exercise intervention in Huntington's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in mouse models of PD have described "gait" by estimating stride length and stance width. 31 Fernagut et al, reported that stride length is a reliable index of motor disorders due to basal ganglia dysfunction in mice. 32 In the present study silybin at both doses (300 and 600mg/kg) reversed the reduction in stride length by MPTP.…”
Section: Histopathological Evaluationmentioning
confidence: 99%
“…Source: Aldridge, 2005. (Hoskyns, 1982) Encourage group participation (Hoskyns, 1982) Counteract anxiety and frustration (Hoskyns, 1982) Increase/maintain movement, increase relaxation, (Rainey Perry, 1983) Providing opportunities for self-expression, encouraging participation (Rainey Perry, 1983) Stimulating communication (Rainey Perry, 1983) Preservation of vocal abilities, demonstrate and maintaining physical strength (Magee, 1995a(Magee, , 1995b Improvement of memory function, organizing information, musical interaction, initiation (Magee, 1995a(Magee, , 1995b Stimulating active participation, avoiding isolation (Magee, 1995a(Magee, , 1995b Gait improvement (Thaut et al, 1999) ecall of information espite memory function terioration (Magee, 1995a(Magee, , 1995b Developing relationship, increasing communicative contact (Davis & Magee, 2001) Modulating velocity (Thaut et al, 1999) Choice making (Magee, 1995a(Magee, , 1995b Stimulating expressive speech (Grocke-Erdonmez, 1976) Reducing involuntary movements/stimulating voluntary movements (Brandt, 2000) Increasing/organizing responses (Magee, 1995a(Magee, , 1995b Preserving expressive and communication skills (Daveson, 2007) Improvement of physical presentation (Daveson, 2007) Improving cognitive skills (Davis & Magee, 2007) Enabling emotional expression (Daveson, 2007) Improving behavior problems (Daveson, 2007) Practice Based Studies Hoskyns (1982) focused on the effects of music therapy on counteracting anxiety and frustration by encouraging relaxation and group participation, and on reducing choreic movement by use of singing, playing, and listening. The most significant findings were that group singing seemed to be very beneficial and that playing musical instruments increased the choreic movement.…”
Section: Benefits Of Music Therapy For the Neurodegenerative Diseasesmentioning
confidence: 99%
“…She did find that several patients were able to sing out words that they had previously had trouble articulation through speech. Thaut, Miltner, Lange, Hurt, and Hoemberg (1999) investigated the rhythmic synchronization ability of 27 HD patients under different conditions and circumstances using the Rhythmic Auditory Stimulation (RAS) techniques. The gait speed of most of the patients could be changed in the direction of the RAS cue.…”
Section: Benefits Of Music Therapy For the Neurodegenerative Diseasesmentioning
confidence: 99%